Macrobenthic community at nesting grounds of horseshoe crabs (Tachypleus gigas and Carcinoscorpius rotundicauda) at Pahang Coast, Malaysia - John, Akbar; Seth, Sihin; Khan Chowdhury, Ahmed Jalal; Yunus, Kamaruzzaman (2011)
Macrobenthos consists of the organisms that live at the bottom of the water column and are visible to the naked eye (usually >0.5mm in size) 2.About 80% of the benthic organisms are Epifauna that are living on or are attached to the surface of rocky areas or firm sediments play an important role in ecosystem processes such as nutrient cycling, pollutant metabolism, dispersion and burial, and in secondary production 3.Macro invertebrate species offers a spectrum of responses to environmental stresses and a broad range of responses to different pollutants 4.The food preferences of horseshoe crabs are well studied from the wild environment while the similar studies are still scanty along their nesting ground